ANALISIS DAN DESAIN SISTEM MONITORING DAN EVALUASI KOPERASI PADA DINAS KOPERASI KABUPATEN SIDOARJO - Usman, Rizka Agustia; Setyawan, Henry Bambang; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Cooperatives are considered the most suitable to be developed in Indonesia because of their role in building the national economic order. Currently Sidoarjo District Cooperative Office for Institutional especially tasked to monitor and oversee the development of the cooperative experience problems. The problem of cooperative is, late submission of monthly reports that resulted in the manufacture of quarterly progress reports as a co-operative evaluation is also inhibited. The delay makes data to be processed to work on a progress report becomes inaccurate. Last problems in the progress report results only in the form of tables with figures that chart the development of cooperatives in the previous month are not visible. After analysis and design of monitoring and evaluation systems of cooperative development document can be produced in the form of Software Requirement Specification (SRS) and the Software Architecture Document (SAD). The document can be used as the basis for monitoring and evaluation of software development at the Department of Cooperative cooperative Sidoarjo RegencyKeywords: Analysis and Design, Monitoring and Evaluation System, SRS and SAD documents.